Patient satisfaction level and its determinants after admission in public and private tertiary care hospitals in Bangladesh - Begum, Farhana; Said, Jamaliah; Hossain, Syed Zabid; Ali, Md. Ayub (Frontiers in Health Services, 2022)
Introduction Patient satisfaction is an important indicator of the quality of care provided by health care facilities. The objective of this study was to investigate the rate of satisfaction and its associated factors among the patients admitted to tertiary care hospitals in Bangladesh. Methods This cross-sectional study was conducted in a public and two private tertiary care hospitals in Bangladesh in December 2019, including 923 consecutive patients admitted to medical and surgical departments. Face-to-face interview using a structured questionnaire was conducted to collect patient-level data. Logistic regression models were used to determine the factors associated with patients' satisfaction. Results Patients' overall satisfaction level was 65% (51% in public and 75% in private hospitals) with a satisfaction rate of 63% in hospital staff courtesy, 56.5% in a hospital environment, 67% in physician care, 63% in general patient satisfaction, and 58% in patient's family care. Private hospitals (aOR 3.64, 95% CI 2.2–6.03), conservative management (aOR 3.34, 95% CI 2.10–5.33), shorter hospital stay (aOR 1.58, 95% CI 1.05–2.37) and perceived improvement after treatment (aOR 1.67, 95% CI 1.01–2.76) were associated with patients' satisfaction. In contrast, patients' accommodation on the floor (aOR 0.38, aOR 0.22–0.66) and high health care costs (aOR 0.97, 95% CI 0.95–0.99) were associated with patients' dissatisfaction with the in-patient service they received in both public and private hospitals. Conclusion Almost two-thirds of the patients were satisfied with the inpatient service they received, though, the satisfaction rate was higher in private hospitals. Treatment modality, cost, and outcome, as well as hospital environment like accommodation, were associated with their satisfaction level.